On periodic solutions of linear degenerate second-order ordinary differential equations - Er’omenko, V. O. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider a scalar linear second-order ordinary differential equation whose coefficient of the second derivative may change its sign when vanishing. For this equation, we obtain sufficient conditions for the existence of a periodic solution in the case of arbitrary periodic inhomogeneity.